2020
DOI: 10.1002/aur.2393
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Language Lateralization in Autism and the Broader Autism Phenotype as Assessed with Robust Individual‐Subjects Analyses

Abstract: One of the few replicated functional brain differences between individuals with autism spectrum disorders (ASD) and neurotypical (NT) controls is reduced language lateralization. However, most prior reports relied on comparisons of group-level activation maps or functional markers that had not been validated at the individual-subject level, and/or used tasks that do not isolate language processing from other cognitive processes, complicating interpretation. Furthermore, few prior studies have examined function… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 144 publications
(195 reference statements)
4
45
2
Order By: Relevance
“…Notably, connectome manifold distortions in autism showed more marked effects in the right hemisphere for idiotypic areas, and more marked effects in the left hemisphere in heteromodal areas. Several prior studies suggested asymmetric findings in autism at the level of cortical morphology as well as functional organization [87][88][89][90][91][92][93] . Our results may contribute to these prior findings by suggesting a differential susceptibility for structural reorganization in autism for left and right hemispheres for unimodal versus heteromodal regions, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, connectome manifold distortions in autism showed more marked effects in the right hemisphere for idiotypic areas, and more marked effects in the left hemisphere in heteromodal areas. Several prior studies suggested asymmetric findings in autism at the level of cortical morphology as well as functional organization [87][88][89][90][91][92][93] . Our results may contribute to these prior findings by suggesting a differential susceptibility for structural reorganization in autism for left and right hemispheres for unimodal versus heteromodal regions, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, the latter finding was even observed by Leo Kanner in 1943 when he noted that five of his 11 cases, “had relatively large heads” (p. 248). Additional findings include abnormal lateralization of the brain with a lack of left lateralization in the structure and function of regions involved with language ( Jouravlev et al, 2020 ; Lindell and Hudry, 2013 ; Nielsen et al, 2014 ), and hypoconnectivity within the default mode network ( Di Martino et al, 2014 ). Furthermore, it has been found that the amygdala initially enlarges but fails to undergo the age-related increase found in typically developing (TD) children, with a larger amygdala predicting more severe symptomatology ( Schumann et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…ASD was most notably associated with widespread alterations of cortical thickness asymmetry, involving the medial frontal, posterior cingulate and inferior temporal cortex. These regions overlapped with those showing altered functional lateralization for language and social cognitive tasks in ASD 11, 12 .…”
Section: Introductionmentioning
confidence: 84%
“…4 ), which included working memory and other executive function-related annotations in common across the networks, but also language-related, reading-related, and sensorimotor annotations. Language delay is a common feature of ASD 5, 6 , and the disorder is also associated with reduced left-hemisphere language dominance 11 . Numerous reports based on behavioral, neurophysiological, neuroimaging or histopathological data have also reported atypical motor system development in ASD 65 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation